The mSQUASH is a feasible and valid measurement tool to uniformly assess daily physical activity in patients with rheumatic diseases - Suzanne Arends; Anneke Spoorenberg; Hendrika Bootsma; Kornelis S M van der Geest; Davy Paap; Lianne Gensler; Karina de Leeuw; Yvonne M van der Kraan; Ellen Thovmasyan; Noa Ausma; Helene Kokol; Marlies Carbo; et al. (RMD Open, 2024)
Background The modified Short QUestionnaire to ASsess Health-enhancing physical activity (mSQUASH) was originally developed and validated in Dutch patients with axial spondyloarthritis (axSpA). To support world-wide distribution, applicability and comparability of measuring physical activity, our aim was to perform translation and cross-cultural adaptation of the mSQUASH into English, field testing in other rheumatic diseases and clinical validation in patients with axSpA.Methods The Dutch mSQUASH was translated into English according to forward–backward Beaton protocol. Semistructured interviews were conducted in representative samples of patients with axSpA (n=13), Sjögren’s disease (n=10), systemic lupus erythematosus (n=10) and giant cell arteritis/polymyalgia rheumatica (n=10) to verify relevance, comprehensiveness and comprehensibility. For construct validity (n=95), Spearman correlations were used with clinical outcome assessments. For test–retest reliability (n=82), intraclass correlation coefficients (ICC) were calculated. For responsiveness (n=80), standardised response means (SRM) were calculated stratified by Anchor method.Results Translation and cross-cultural adaptation of the mSQUASH into English were successfully carried out, which can serve as basis for other translations. Only minor adaptations and clarifications were implemented. Fair correlations were found between mSQUASH and Axial Spondyloarthritis Disease Activity Score (ρ=−0.31), Bath Ankylosing Spondylitis Functional Index (ρ=−0.37) and Assessment of SpondyloArthritis International Society-Health Index (ρ=−0.30). Test–retest reliability was very good (ICC: 0.87). Responsiveness corresponded to the direction of self-reported changes in physical activity (SRM: 0.72 for improved, 0.06 for stable and −0.74 for worsened).Conclusion The mSQUASH showed good linguistic and face validity according to field testing in different rheumatic diseases. Clinical validation confirmed good construct validity, test–retest reliability and responsiveness in patients with axSpA, which supports the use of the mSQUASH in clinical practice and research.